SIFAT FISIKA PAPAN SEMEN PARTIKEL DARI SERBUK GERGAJI KAYU KEMPAS (Koompasia malaccensis Maing) - Arniwati; Wulandari, Febriana Tri; Lestari, Andi Tri (Jurusan Kehutanan, 2022)
The increasing demand for wood and the diminishing potential of forests necessitate the efficient and prudent use of wood resources. To address this issue, alternatives to wood are required, and one such option is particleboard made from wood sawdust. The abundance of waste sawdust from kempas wood (Koompassia malaccensis Maing) is noteworthy, yet this waste material remains underutilized. The objective of this research is to determine: i.) the influence of the particle-to-cement ratio, ii.) the effect of different compressive pressures on the physical properties of kempas wood sawdust particleboard, and iii.) the interaction between the particle-to-cement ratio and compressive pressure on the physical properties of kempas wood sawdust particleboard. In this study, a factorial completely randomized design with two factors was employed. The first factor is the particle-to-cement ratio (P), consisting of three levels: P1 (1:3), P2 (1:4), and P3 (1:5). The second factor is the difference in compressive pressure (T), comprising two levels: T1 (25 kg/cmÂ²) and T2 (35 kg/cmÂ²). There are a total of 6 treatments resulting from the combination of these two factors, repeated three times, and yielding 18 test samples. The results indicate that the ratio of cement to particles only significantly affects density at a significance level of 0.05 but does not impact moisture content and thickness swelling of kempas wood sawdust particleboard. The variation in compressive pressure does not influence any of the physical properties (density, moisture content, and thickness swelling) of the particleboard. Furthermore, the interaction between the particle-to-cement ratio and compressive pressure does not significantly affect any of the physical properties (density, moisture content, and thickness swelling) of kempas wood sawdust particleboard.